Blunt abdominal injury: a rare cause for delayed small bowel obstruction - Shahid, Mohammed; Hanumanthaiah, K. S.; Venkatesh, S. (International Surgery Journal, 2019)
Blunt abdominal trauma is a cause of acute abdomen leading to visceral injury and shock. Intestinal obstruction though rare has been a known complication of blunt abdominal trauma. We present to a case of a blunt abdominal trauma leading to delayed intestinal obstruction 4 weeks after primary injury. We present to you a case of blunt abdominal trauma leading to delayed intestinal obstruction 4 weeks after primary injury.